2018
DOI: 10.2516/ogst/2018057
|View full text |Cite
|
Sign up to set email alerts
|

Production improvement in gas condensate reservoirs by wettability alteration, using superamphiphobic titanium oxide nanofluid

Abstract: Many gas condensate reservoirs suffer a loss in productivity owing to accumulation of liquid in near-wellbore region. Wettability alteration of reservoir rock from liquid-wetting to gas-wetting appears to be a promising technique for elimination of the condensate blockage. In this paper, we report use of a superamphiphobic nanofluid containing TiO2 nanoparticles and low surface energy materials as polytetrafluoroethylene and trichloro(1H,1H,2H,2H-perfluorooctyl)silane to change the wettability of the carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In the EOR processes, the addition of TiO 2 NPs to the injected fluid is capable of altering rock wettability and preventing asphaltene precipitation [18]. However, it has been reported that exceeding the optimum concentration does not necessarily improve the situation.…”
Section: Ph Of Solutionmentioning
confidence: 99%
“…In the EOR processes, the addition of TiO 2 NPs to the injected fluid is capable of altering rock wettability and preventing asphaltene precipitation [18]. However, it has been reported that exceeding the optimum concentration does not necessarily improve the situation.…”
Section: Ph Of Solutionmentioning
confidence: 99%
“…As mentioned earlier, wettability alteration to the gas-wetting in the near-wellbore zone is a solution to remove condensate formed in the area. To illustrate the relationship between gas wettability and condensate removal in this area, it should be noted that condensates in this area can be eliminated by increasing the drawdown pressure (viscous forces) or lowering capillary pressure (Esmaeilzadeh et al 2018). The capillary pressure (P c ) is proportional to contact angle (θ), gas-liquid surface tension ( ) and reversely proportional to pore size (r), according to Young-Laplace equation (Eq.…”
Section: Surface Tension and Contact Angle Resultsmentioning
confidence: 99%
“…2): Capillary pressure can be decreased by either reducing the gas-liquid surface tension or increasing the contact angle through wettability alteration. By these interpretations, and by keeping the gas-liquid surface tension constant, the wettability alteration to the gas-wetting reduces capillary pressure and eliminates condensate in the area (Esmaeilzadeh et al 2018).…”
Section: Surface Tension and Contact Angle Resultsmentioning
confidence: 99%
“…They also showed that altering the wettability led to an increment of oil production from 45.6% to 78.4% and consequently the saturation of remaining oil decreased from 29.2% to 17.8%. For altering the tendency of the carbonate rock from highly liquid-wetting toward ultra gaswetting, TiO 2 nanoparticles were modified using PTFE and PFOS by Esmaeilzadeh et al 117 SEM and stylus profilometer (SP) tests were conducted to indicate the adsorption process. Their results indicated an improvement in the productivity of both liquids and gas after treatment.…”
Section: Chemically Induced Wettability Alterationmentioning
confidence: 99%